Value of schizophrenia treatment II: Decision modelling for developing early detection and early intervention services in the Czech Republic - Winkler, Petr; Broulíková, Hana Marie; Kondrátová, Lucie; Knapp, Martin; Arteel, Paul; Boyer, Patrice; Galderisi, Silvana; Karkkainen, Hikka; Ieven, Aagje; Mohr, Pavel; Wasserman, Danuta; Park, A-La; et al. (European psychiatry, 2018)
BACKGROUND: Positive findings on early detection and early intervention services have been consistently reported from many different countries. The aim of this study, conducted within the European Brain Council project "The Value of Treatment", was to estimate costs and the potential cost- savings associated with adopting these services within the context of the Czech mental health care reform. METHODS: Czech epidemiological data, probabilities derived from meta-analyses, and data on costs of mental health services in the Czech Republic were used to populate a decision analytical model. From the health care and societal perspectives, costs associated with health care services and productivity lost were taken into account. One-way sensitivity analyses were conducted to explore the uncertainty around the key parameters. RESULTS: It was estimated that annual costs associated with care as usual for people with the first episode of psychosis were as high as 46 million Euro in the Czech Republic 2016. These annual costs could be reduced by 25% if ED services were adopted, 33% if EI services were adopted, and 40% if both, ED and EI services, were adopted in the country. Cost-savings would be generated due to decreased hospitalisations and better employment outcomes in people with psychoses. CONCLUSIONS: Adopting early detection and early intervention services in mental health systems based on psychiatric hospitals and with limited access to acute and community care could generate considerable cost- savings. Although the results of this modelling study needs to be taken with caution, early detection and early intervention services are recommended for multi-centre pilot testing accompanied by full economic evaluation in the region of Central and Eastern Europe.
Keywords: Česká republika; Schizophrenia; schizofrenie; psychotické poruchy; služby péče o duševní zdraví; Humans; Mental Health Services; náklady na zdravotní péči; Health Care Costs; analýza nákladů a výnosů; Czech Republic; časná diagnóza; Decision Support Techniques; hospitalizace; Hospitalization; lidé; metody pro podporu rozhodování; Early Diagnosis; Psychotic Disorders; Cost-Benefit Analysis